HPLC를 이용한 조제유류 중 베타카로틴 함량 분석 연구 - 황경미; 배지원; 허수정; 오금순; Hwang, Kyung Mi; Bae, Ji Won; Hu, Soo Jung; Oh, Keum Soon (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2019)
A procedure based on high-performance liquid chromatography (HPLC) is described to determine ${β}-carotene$ in infant formulas. The method for ${β}-carotene$ analysis was performed on a C18 reversed-phase column using acetonitrile/methanol/dichloromethane (6:1:3, v/v/v) as a mobile phase. ${β}-Carotene$ was determined in HPLC with photo diode array (PDA) detector. The parameters of validation were specificity, linearity, LOD, LOQ, accuracy, precision and repeatability. The specificity was confirmed by the retention time and the linearity ($R^2$), which was over 0.999 in the range of 0.125~2 mg/L. The detection and quantification limits were 0.064 and 0.193 mg/L, respectively. The accuracy and precision of this method using an STD spiked sample were 80~119% and 1.02~2.05% respectively. The method was applied to the analysis of various infant formula and follow-up formulas products containing ${β}-carotene$, and all the products contained acceptable levels of ${β}-carotene$ for nutrition labeling. 본 연구는 조제유류 중 "식품의 기준 및 성분규격"에 기준 규격이 설정되어 있지 않으나 제품에 함유되어 있는 베타카로틴에 대해 분석법을 마련하고자 수행하였다. 조제유류에 함유된 베타카로틴 함량 분석을 위해 HPLC를 이용한 분석법을 확립하고 시중에 유통 중인 제품을 대상으로 적용성을 검토하였다. 베타카로틴 표준품을 이용하여 HPLC를 이용한 기기분석조건을 확립하고 시료 중의 베타카로틴을 추출하여 분석하였다. 분석법 검증은 특이성, 직선성, 검출한계 및 정량한계, 정확성, 정밀성에 대해 수행되었다. 0.125~2 mg/L의 농도범위에서 $R^2=0.999$ 이상의 우수한 직선성을 확인할 수 있었으며, LOD와 LOQ는 각각 0.1, 0.2 mg/L였다. 표준물질 첨가법을 이용하여 정확성을 검토하였으며, 81~120%의 회수율을 확인할 수 있었다. 정밀성을 검토한 결과 시료 채취량에 따른 반복성은 RSD값이 2.1~4.9%, 실험실간 교차검증을 통한 실험일자에 따른 재현성은 4.0 RSD(%)로 확인되었다. 본 연구에서 확립된 분석법을 적용하여 조제유류 13건, 성장기용조제식 7건 등 국내 유통 중인 제품 20건에 대해 적용성 검토를 실시한 결과 전체 시료에서 분석이 용이하였으며, 모두 표시기준에 적합함을 확인하였다.